Evaluation of the performance of pressure retarded osmosis (pro) membrane modules and systems for renewable energy recovery - Ang, Pancy (2016)
Pressure retarded osmosis (PRO) is an osmotically-driven membrane process (ODMP) to recover renewable osmotic energy from salinity gradients. This project aims to evaluate performance of PRO membrane modules and systems for osmotic energy recovery. Numerical models were developed to simulate hollow fibre module performance. The effects of flow configuration (i.e., co-current vs counter-current flow of draw solution (DS) and feed solution (FS)), hollow fibre module parameters (i.e., fibre diameter and module length), DS and FS flow rate on module performance were investigated. Different configurations for connecting a group of modules were designed and their performance were evaluated. Three possible designs of PRO system were developed and compared for their performance. The results obtained shown that smaller module diameter, shorter module length, draw flow rate 6000L/h, feed flow rate 6000L/h and counter-current configuration rendered a better PRO module performance, defined by a higher peak !"#$. Parallel module configuration in PRO system design 3 provided the highest overall PRO system performance with !%" = 3.67+,. This was due to additional ERDs to recover hydraulic pressure energy generated. While this research aims to determine which PRO module configuration and PRO system design has the highest PRO system performance, future research can use the developed model and simulation results to optimize PRO system design and parameters. Additionally, investigation of performance of PRO hollow fibre (HF) modules in a PRO pilot plant must be carried out to verify the numerical modeling results obtained in this research.